Analisis Peluang dan Tantangan Digitalisasi Akuntansi Syariah pada Lembaga Keuangan Syariah di Indonesia - Edrial Tri Putra; Andi Muh. Adam; Fharel Fharel; Masyhuri Masyhuri (INDO PUBLISHING, 2026)
The development of digital technology has driven significant transformation in the financial sector, including Islamic financial institutions in Indonesia. This transformation has also influenced the practice of Islamic accounting, which plays an important role in providing transparent, accurate, and Sharia-compliant financial information. This article aims to examine the opportunities and challenges arising from the implementation of digitalization in Islamic accounting within Islamic financial institutions in Indonesia. The study employs a qualitative approach through a literature review by analyzing various scientific publications, regulations, and related references. The findings indicate that digitalization offers several opportunities, including improved operational efficiency, faster data processing, enhanced quality of financial reporting, and greater ease in monitoring and decision-making processes.